Integration simulation and control practice of a designed electric fertilization device for adapting different plant spacings - Yuan, Xianju; Zhang, Lei (International Journal of Agricultural and Biological Engineering, 2025)
Effective adjustment of fertilization spacing and amounts for different plant distances is beneficial to increase production and reduce the amount of fertilizer used. In order to achieve such a target, an electric-fertilizing vehicle with staggered fan-shaped openings in a fertilization device is proposed here, and its fertilization spacing and amounts are controlled by a control system and mobile phone-based programs. Further validating multivariable effects on fertilization spacing and amounts, such as openings, rotary speeds, and moving parameters of the vehicle, an integration discrete element model (DEM) is established so that the feasibility of the fertilization device could be evaluated before manufacturing and testing. Finally, it is reflected through field-simulated experiments that fertilizer spacing ranges from 0.27 to 5.45 m. Compared with simulated results, the absolute error varies from −0.08 to 0.05 m, and the maximum relative error is about −5.67%. Therefore, the uniform and stable fertilization for different plant spacing is semi-actively achieved by the designed device and a control system with mobile phone-based programs. The proposed simulation model is feasible, thus presenting a good reference for designing these components. Key words: electric-fertilizing vehicle; staggered fan-shaped openings; mobile phone-based program; varied spacing fertilization; DEMDOI: 10.25165/j.ijabe.20251802.8296Citation: Yuan X J, Zhang L. Integration simulation and control practice of a designed electric fertilization device for adaptingdifferent plant spacings. Int J Agric & Biol Eng, 2025; 18(2): 124–131.